Letter - T&GWU etc Joint Committee, Woolwich, 10 May 1926 (page 2)
1926-05-10 "Letter - T&GWU etc Joint Committee, Woolwich, 10 May 1926 (page 2)" [g0256002.jpg], 10 May 1926, Transport and General Workers' Union